2020
DOI: 10.3390/app10030745
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Model Predictive Control for Hydraulic Hybrid Powertrain of a Construction Vehicle

Abstract: Hybrid hydraulic technology has the advantages of high-power density and low price and shows good adaptability in construction machinery. A complex hybrid powertrain architecture requires optimization and management of power demand distribution and an accurate response to desired power distribution of the power source subsystems in order to achieve target performances in terms of fuel consumption, drivability, component lifetime, and exhaust emissions. For hybrid hydraulic vehicles (HHVs) that are used in cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Liu et al proposed an improved equivalent fuel consumption minimization strategy (ECMS) for a hybrid electric vehicle, where the fuel economy can be improved by adjusting the engine operating point to a high-efficiency zone during the acceleration process [14]. In terms of the adaptive control strategy, Wang et al presented a stochastic model predictive control (SMPC)-based energy management, to improve the operating points distribution of an engine [15]. Liu et al proposed an adaptive hierarchical energy management for a PHEV, which can prevent the engine from operating in the inefficient zone while reducing the fuel consumption of the vehicle [16].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al proposed an improved equivalent fuel consumption minimization strategy (ECMS) for a hybrid electric vehicle, where the fuel economy can be improved by adjusting the engine operating point to a high-efficiency zone during the acceleration process [14]. In terms of the adaptive control strategy, Wang et al presented a stochastic model predictive control (SMPC)-based energy management, to improve the operating points distribution of an engine [15]. Liu et al proposed an adaptive hierarchical energy management for a PHEV, which can prevent the engine from operating in the inefficient zone while reducing the fuel consumption of the vehicle [16].…”
Section: Introductionmentioning
confidence: 99%
“…During these untrained evaluation cycles the NN controller was able to decrease average fuel consumption by 25.8 % when compared to a baseline constant pressure control strategy. Wang and Jiao 21 a hierarchical model predictive control (MPC) scheme is presented in this paper using the example of a spray-painting construction vehicle. The upper layer is a stochastic MPC (SMPC) based energy management control strategy (EMS) and the lower layer is an MPC-based tracking controller with disturbance estimator of the diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…The design, assembly and testing of the system prototype showed that the efficiency of the system was improved accordingly and that the proposed method was feasible. Wang et al [13] combined the high energy density of hydraulic accumulators and designed a strategy to improve fuel economy. The results show that the average fuel consumption per gallon of the proposed strategy, compared with the rule-based control strategy and the proportional integral derivative controller-based control strategy, increased by 7.3% and 5.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%